2014
DOI: 10.2989/16085914.2014.925419
|View full text |Cite
|
Sign up to set email alerts
|

Prawn community structure in the subtropical Mfolozi–Msunduzi estuarine system, KwaZulu-Natal, South Africa

Abstract: The life cycles of many marine and freshwater prawn species are closely associated with estuarine habitat. Here, the prawn community of the Mfolozi-Msunduzi estuarine system is described and the system's potential as an alternative nursery for prawns during prolonged closure of the adjacent St Lucia estuarine system is examined. Sampling was conducted at five localities in summer and winter in 2007-2012. The Mfolozi-Msunduzi Estuary is a river-dominated system with mouth condition, sediment grain size and turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…At the genus level, it was found that Macrobrachium from Palaemonidae was the most affected by salinity gradients and can be considered as the key indicator of water salinity. This corroborates the findings of other studies, which indicate that the life cycle or style of Macrobrachium is mainly related to estuary or water salinity (N'Zi et al, 2008;Collocott et al, 2014;Gangbe et al, 2016;Chen et al, 2018;Adam et al, 2019). Meanwhile, Mollusca taxon is associated with water eutrophication due to organic pollution.…”
Section: Response Of Macroinvertebrates At Different Taxonomic Levelssupporting
confidence: 92%
See 1 more Smart Citation
“…At the genus level, it was found that Macrobrachium from Palaemonidae was the most affected by salinity gradients and can be considered as the key indicator of water salinity. This corroborates the findings of other studies, which indicate that the life cycle or style of Macrobrachium is mainly related to estuary or water salinity (N'Zi et al, 2008;Collocott et al, 2014;Gangbe et al, 2016;Chen et al, 2018;Adam et al, 2019). Meanwhile, Mollusca taxon is associated with water eutrophication due to organic pollution.…”
Section: Response Of Macroinvertebrates At Different Taxonomic Levelssupporting
confidence: 92%
“…From this study, crustaceans were found to be good indicators of the freshwater salinity. Indeed, crustaceans were dominated by two families (Palaemonidae and Atyidae) and well known to be influenced by EC or water salinity (Attrill et al, 1999;Cuesta et al, 2006;N'Zi et al, 2008;Collocott et al, 2014). At the genus level, it was found that Macrobrachium from Palaemonidae was the most affected by salinity gradients and can be considered as the key indicator of water salinity.…”
Section: Response Of Macroinvertebrates At Different Taxonomic Levelsmentioning
confidence: 99%
“…3). A similar study conducted by Collocott et al (2014) and De Sousa et al (2020) showed summer months favor a high abundance of freshwater prawns and marine prawns, e.g., Farfantepenaeus brasiliensis, respectively.…”
Section: Variation In Abundance Of Prawn Speciesmentioning
confidence: 53%
“…Seasonal changes in salinity driven by variations in freshwater discharge result in shifts in biological communities (Collocott et al, 2014), promoting species diversity by controlling dominant species, such as the mangrove Kandelia obovate in the Tanshui River estuary, Taiwan, allowing for succession (Shih et al, 2011). These fluctuations may also facilitate adaptation to highly varying salinity conditions, promoting species with wide distributions and competitive advantages (Sheaves, 1998).…”
Section: Salinity Regulationmentioning
confidence: 99%